A global challenge and a legal requirement: new findings can help the Welsh response and put sustainable development into practice. (11th May 2020) - Weatherup, Cathy; Azam, Sumina
Abstract: Sustainable development legislation in Wales requires us to think and act differently to contribute to seven well being goals, namely; prosperity, resilience, health, equity, cohesive communities, globally responsible and a vibrant culture and thriving welsh language, now and over the longer term. Findings from a Literature Review, commissioned by the Health and Sustainability Hub, Public Health Wales, identify approaches and recommendations to help implement the legislation; aimed at people, policies and practice.